Beyond Gridlock - Vandenbergh, Michael P.; Gilligan, Jonathan A. (Columbia Journal of Environmental Law, 2019)
Private climate governance can achieve major greenhouse gas (“GHG”) emissions reductions while governments are in gridlock. Despite the optimism that emerged from the Earth Summit in Rio de Janeiro, Brazil in 1992, almost a quarter century later the federal legislative process and international climate negotiations are years from a comprehensive response. Yet Microsoft, Google and many other companies have committed to become carbon neutral. Wal-Mart has partnered with the Environmental Defense Fund to secure 20 million tons of GHG emissions reductions from its suppliers around the world, an amount equal to almost half the emissions from the US iron and steel industry. Investors holding roughly $90 trillion in assets have pressured large corporations to disclose and reduce their carbon footprints, and participating companies report having reduced emissions by an amount equal to a major emitting nation. Private forest certification programs have taken steps to reduce the GHG emissions from deforestation. Household carbon regulation is off the table in many countries, but private advocacy groups and corporations have reduced household emissions through home energy disclosure, eco-driving campaigns, employee programs, voluntary carbon offsets, and other initiatives. To explain the importance of private climate governance, this Article is structured around three propositions. The first is the need for urgency... The second proposition is that the barriers to adopting and implementing a carbon price are unlikely to be overcome in the next decade... The third proposition is that unlocking the potential of private governance will require a conceptual shift by scholars, philanthropists, and corporate and NGO managers... Private initiatives cannot keep global emissions on track to achieve the most widely adopted climate target, but they can achieve a private governance wedge: they can reduce emissions by roughly 1,000 million tons (a gigaton) of CO2 per year between 2016 and 2025. When combined with other efforts, this private governance wedge offers a reasonable chance of buying a decade to resolve the current government gridlock.